Peran Literasi Keuangan Syariah dalam Meningkatkan Adopsi Fintech dan Keuangan Digital: Implikasi terhadap Inklusi Keuangan Syariah di Provinsi Aceh - Budi, M. Arief Setia; Andi, Muhammad; Farizal, Ryan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study investigates the role of fintech and digital finance as intermediary variables in the influence of sharia financial literacy on increasing sharia financial inclusion in Aceh Province. This study examined 308 respondents spread across various regions of Aceh Province and analyzed using SEM AMOS and a purposive sampling technique. After conducting various tests, this study demonstrated that sharia financial literacy, fintech, digital finance, and sharia financial inclusion have been well-functioning. Sharia financial literacy has been proven to enhance fintech, digital finance, and sharia financial inclusion in Aceh. Correspondingly, fintech and digital finance also have a positive and significant impact on sharia financial inclusion. Furthermore, fintech and digital finance have also been shown to partially mediate the relationship between sharia financial literacy and sharia financial inclusion